Analysis of the relationship between the population size of Kalimantan orangutan (Pongo pygmaeus) and land cover changes in Central Kalimantan, Indonesia - ELISABETH BEWA LODANARITA OPENG; YANTO SANTOSA; I NENGAH SURATI JAYA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Openg EBL, Santosa Y, Jaya INS. 2024. Analysis of the relationship between the population size of Kalimantan orangutan (Pongo pygmaeus) and land cover changes in Central Kalimantan, Indonesia. Biodiversitas 25: 3468-3475. Land cover change, a major driver of habitat change, significantly influences the distribution of wildlife species, including the Kalimantan orangutan (Pongo pygmaeus Linnaeus, 1760) in Central Kalimantan, Indonesia. This analysis, aimed at quantitatively assessing the relationship between changes in land cover and the population of Kalimantan orangutans in 2014-2019, underscores the urgent need for orangutan conservation. Using data on the population of Kalimantan orangutans and updated Landsat images with land cover data from the Indonesian Ministry of Environment and Forestry, we conducted a multiple linear regression analysis to unveil the relationship between the two. The research results from three specific conservation area locations reveal a decrease in the orangutan population in Lamandau, with the largest increase in open land cover types, a trend largely influenced by anthropogenic factors. Conversely, an increase in population was observed in Sebangau, with the largest increase in the swamp land cover type, and population fluctuations occurred in Tanjung Puting, with the largest increase in the open land cover type. The decline in the orangutan population is attributed to anthropogenic factors and natural predators, while the population increase occurs naturally and through orangutan reintroduction activities. The analysis concludes that secondary swamp forests, bushes, and open land cover are closely related to the size of the Kalimantan orangutan population at the research location, thereby highlighting the urgency and concern for orangutan conservation.